Modulation of leaf attributes and water use efficiency in Quercus suber along a rainfall gradient - Gouveia, António C.; Freitas, Helena (Trees, 2008)
The aim of our study was to assess the intraspeciﬁc variation of a range of leaf attributes and carbon isotope discrimination (D), in Quercus suber, along an 800 mm rainfall gradient in Portugal. We measured speciﬁc leaf area (SLA), leaf thickness (LT) and density, and used leaf carbon isotope content as an integrated record of water use efﬁciency. The values of SLA of Q. suber were strongly, positively correlated with rainfall, decreasing as rainfall decreased. This reduction was mainly driven by LT, which was tightly correlated with SLA (R = -0.80, P\0.001), and steadily increased with declining rainfall. The signiﬁcant increase in carbon isotope discrimination towards the wetter end of the gradient, with a difference of 4.2% in D between the two extremes, suggests a strong adjustment of leaf gas exchange to water availability. Leaf changes associated with precipitation in Q. suber thus seem to inﬂuence water economy, since reduction of SLA with the increase of LT with aridity improves water use efﬁ- ciency. These data suggest that this evergreen tree species relies on its foliage plasticity and physiology to overcome water shortage.
Keywords: carbon isotope discrimination; carbon isotope discrimination á; evergreen tree; evergreen tree á; leaf plasticity; leaf plasticity á; rainfall gradient

Carbon isotope discrimination in Quercus ilex resprouts after fire and tree-fell - Fleck, Isabel; Grau, Daniel; Sanjose, M.; Vidal, D. (Oecologia, 1996)
Ecophysiological differences related to photo- synthesis were compared in holm oak Quercus ilex leaves from undisturbed holm-oak vegetation, resprouts after fire and resprouts after tree-fell. No significant dif- ferences in any parameter measured were observed be- tween the two kinds of resprout throughout the first growing season following disturbance. Resprouting leaves showed lower carbon isotope discrimination (A) and intercellular CO 2 concentration (Pi), and higher pho- tosynthesis, leaf conductance and transpiration rates than leaves from undisturbed stands. Nitrogen, soluble protein content and ribulose bisphosphate carboxylase (RuBP- Case) activity were 88%, 96% and 45% higher respec- tively, in both kinds of resprout. The results indicate that photosynthetic capacity, rather than stomatal conduc- tance, is the limiting factor in photosynthesis in re- sprouts. Chlorophyll content and chlorophyll a/b ratio did not differ between resprouts and undisturbed leaves, indicating that the observed differences were not a result of differences in light environment during leaf develop- ment. Leaf mass per area (LMA), was 80% higher in the resprouts, and was negatively related (r= -0,86) to A and positively related (r=0.87) to N content. Enhanced car- bon assimilation after disturbances resulted in higher wa- ter use efficiency, as indicated by lower A values in the resprouts. We conclude that the cause of defoliation was not relevant in the physiology of the resprouts, suggest- ing the importance of underground organs.
Keywords: carbon isotope discrimination; Fire and tree-fell resprouts; Gas exchange; RuBPCase activity